Non-invasive diagnosis of liver fibrosis in chronic hepatitis C - Schiavon, Leonardo de Lucca (2014)
Assessment of liver fibrosis in chronic hepatitis C virus (HCV) infection is considered a relevant part of patient care and key for decision making. Although liver biopsy has been considered the gold standard for staging liver fibrosis, it is an invasive technique and subject to sampling errors and significant intra-and inter-observer variability. Over the last decade, several noninvasive markers were proposed for liver fibrosis diagnosis in chronic HCV infection, with variable performance. Besides the clear advantage of being noninvasive, a more objective interpretation of test results may overcome the mentioned intra-and inter-observer variability of liver biopsy. in addition, these tests can theoretically offer a more accurate view of fibrogenic events occurring in the entire liver with the advantage of providing frequent fibrosis evaluation without additional risk. However, in general, these tests show low accuracy in discriminating between intermediate stages of fibrosis and may be influenced by several hepatic and extrahepatic conditions. These methods are either serum markers (usually combined in a mathematical model) or imaging modalities that can be used separately or combined in algorithms to improve accuracy. in this review we will discuss the different noninvasive methods that are currently available for the evaluation of liver fibrosis in chronic hepatitis C, their advantages, limitations and application in clinical practice. (c) 2014 Baishideng Publishing Group Co., Limited. All rights reserved.